The identification of gene ontologies and candidate genes for digital dermatitis in beef cattle from a genome-wide association study - G Kopke; K Anklam; M Kulow; L Baker; HH Swalve; FB Lopes; GJM Rosa; D Döpfer (International Journal of Veterinary Science and Research - Peertechz Publications, 2020)
Bovine Digital Dermatitis (DD) is an infectious disease causing severe lameness in cattle. The aim of this study was to perform a Genome Wide Association Study (GWAS) and a Gene-Set Enrichment Analysis (GSEA) to identify candidate genes, instead of an individual Single Nucleotide Polymorphism (SNP), associated with DD traits in beef cattle. Beef cattle (n= 307) were genotyped with the Illumina GGP-HD bovine 150K SNP chip. The M-scores of the cattle over the observation period were used to define the DD traits with different complexities, the distinction between affected (1) and unaffected (0) cattle, regarding the general DD-status (DD AFFECTED), acute disease events (DD ACUTE), visible signs of chronicity (DD CHRONICITY) and proliferation of the skin (DD PROLIFERATION). The gene-set enrichment analysis revealed 30 Gene Ontology (GO) terms associated with the DD AFFECTED trait and 17, 31, and 16 GO terms were associated with DD ACUTE, DD CHRONICITY, and DD PROLIFERATION traits, respectively. By searching the significantly enriched GO terms from the ontology categories, biological process and cellular components, and molecular function, 25 functional genes were identified that were highly involved in cellular and membrane function pertaining to adhesion, migration and proliferation which could contribute to DD traits. These results could provide insight into the genetic framework of this complex trait and disease in beef cattle to aid the development of potential genetic therapies as well as selective breeding strategies to decrease DD prevalence in cattle.